Utilization of media in distributing public information in Negeri Liang, Central Maluku - Rumra, Fatmawaty; Waliulu, Yuniar Sakinah (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyse the use of media in disseminating public information in Liang Village, Central Maluku Regency. Public information disclosure is a crucial aspect in realizing transparent, accountable, and participatory governance. The research method employed was a qualitative approach, utilizing data collection techniques that included interviews, observations, and documentary studies. The results show that the Liang Village government utilizes various communication media, both traditional and digital. Traditional media that are still predominantly used include village announcement boards, mosque and church loudspeakers, and face-to-face meetings. Meanwhile, digital media such as WhatsApp groups and social media are beginning to be used to accelerate the flow of information, especially among the younger generation. However, several obstacles remain, including limited internet access, low digital literacy among some members of the public, and a strong reliance on conventional communication methods. This study recommends optimizing the use of digital media in a more structured manner, enhancing the technological literacy of civil servants, and collaborating with community leaders to expand the reach of public information. Thus, appropriate media utilization can improve the effectiveness of government communication and strengthen public participation in national development.